Proccedings of International Scientific Conference "RURAL DEVELOPMENT 2017" 2018
DOI: 10.15544/rd.2017.034
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Usb-Moisture Meter for Seeds of Agricultural Crops

Abstract: The modern technical development condition is closed due to tough business competitiveness, so the innovative information for teaching students on the best examples of engineering and designing is not available. This is one of the basic reasons that diminish engineering education effectiveness in the field of technical knowledge in modern agricultural production. The scientists of engineering departments work above the solution of this problem and adapt the results into practice-oriented teaching technologies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The results of experimental studies are shown in Tables 2 and 3. The values of Vsminand Vsmaxare determined by the formulas (8): (8) where TOPthe PWM3 resolution.…”
Section: Resultsmentioning
confidence: 99%
“…The results of experimental studies are shown in Tables 2 and 3. The values of Vsminand Vsmaxare determined by the formulas (8): (8) where TOPthe PWM3 resolution.…”
Section: Resultsmentioning
confidence: 99%
“…All microcontrollers contain, as a rule, at least two hardware binary counters of rectangular pulses. This allows organizing a fixed time interval (a gate time) on one counter, and on the other -to count the pulses received at its input during this time interval.The NE555 mathematical model is included in the popular at engineering faculties Multisim http://www.ni.com/multisim simulation environment for designing of electronic devices [1].…”
Section: Methodsmentioning
confidence: 99%
“…Microcontroller metering converter of capacitance (MMCC) was considered in [1]. The MMCCbased USB-moisture meter for seeds of agricultural crops was developed.The MMСC output signal is the frequency that depends on the capacity of the sensor in the cavity of which seeds are located.…”
Section: Introductionmentioning
confidence: 99%